Mental Fatigability and Heart Rate Variability in Mild Cognitive Impairment - Lin, Feng (Am J Geriatr Psychiatry, 2016)
OBJECTIVES: Adaptive physiological stress regulation is rarely studied in mild cognitive impairment (MCI). Here we targeted mental fatigability (MF) as a determinant of altered high frequency heart rate variability (HF-HRV) reactivity in individuals with MCI, and examined fronto-basal ganglia circuitry as a neural basis supporting the link between MF and HF-HRV reactivity. METHODS: We measured mental fatigability and HF-HRV during a 60-minute cognitive stress protocol in 19 individuals with MCI. HF-HRV responses were modeled using a quadratic equation. Resting state functional connectivity of intra- and inter-network fronto-basal ganglia circuitry was assessed using blood-oxygen-level dependent MRI among 7 of the participants. RESULTS: Lower MF was associated with faster and greater rebound in U-shape HF-HRV reactivity, which linked to a stronger connectivity between right middle frontal gyrus and left putamen. CONCLUSIONS: Results suggest that MF may contribute to abnormal physiological stress regulation in MCI, and fronto-basal ganglia circuitry may support the link.